2020
DOI: 10.3390/cancers12020496
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Micro-RNA-23a Mediates Chemoresistance to Cytarabine in Acute Myeloid Leukemia

Abstract: Resistance to chemotherapy is one of the primary obstacles in acute myeloid leukemia (AML) therapy. Micro-RNA-23a (miR-23a) is frequently deregulated in AML and has been linked to chemoresistance in solid cancers. We, therefore, studied its role in chemoresistance to cytarabine (AraC), which forms the backbone of all cytostatic AML treatments. Initially, we assessed AraC sensitivity in three AML cell lines following miR-23a overexpression/knockdown using MTT-cell viability and soft-agar colony-formation assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…Although novel targeted treatment approaches have been developed for patients with AML, their prognosis is still dismal with 5-year-survival rates of 40%-45% in patients below the age of 65 years and less than 20% in patients aged 65 years or older [7,15]. Relapsed disease as a consequence of diverse molecular aberrations affecting dormant LSCs is the main reason for this dismal outcome [16][17][18][19][20]. In AML, parameters influencing treatment decisions as well as outcome include both patient-specific characteristics and leukemia-specific aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…Although novel targeted treatment approaches have been developed for patients with AML, their prognosis is still dismal with 5-year-survival rates of 40%-45% in patients below the age of 65 years and less than 20% in patients aged 65 years or older [7,15]. Relapsed disease as a consequence of diverse molecular aberrations affecting dormant LSCs is the main reason for this dismal outcome [16][17][18][19][20]. In AML, parameters influencing treatment decisions as well as outcome include both patient-specific characteristics and leukemia-specific aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang Y et al found that the proliferation of hepatocellular carcinoma cells is promoted by the miR-23a-Stat5A-Akt signaling pathway[ 22 ]. Consistent with solid tumor studies, miR-23a has been reported to mediate cytarabine resistance in AML cells by targeting the TOP2B gene and to correlate with the relapsed/refractory stage[ 23 ]. However, other authors have validated that miR-23a is involved in the inhibition of tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, we found that overexpressed MEG3 could promote the sensitivity of AML cells to AraC. AraC is the key element of all cytostatic AML treatments [ 29 ]. The theoretical basis for AraC therapy was developed in the 1970s and has since been utilized in AML treatment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%